Professional values education for undergraduate nursing students: developing a framework based on the professional values growth theory - Jialin Li; Xiaohan Li (BMC, 2024)
Background Education has been recognised as necessary in forming and internalising professional values. The system and instructors' content in existing educational institutions focus on developing students' knowledge, skills and practices. Still, the development of values has yet to achieve significant effects, leading to a crisis in students' professional identity. Aims To construct a professional values growth theory for undergraduate nursing students and develop a corresponding education framework. Methods Through the review, some databases(PubMed、CINAHL、Web of Science、Wiley and Google Scholars)were searched using a systematic search strategy to collect relevant literature on professional values education. Based on the nursing professional values growth theory (Li and Li, Nursing Ethics In press, 2022), a theory of professional values growth of nursing undergraduates was developed using the method of theory derivation. Two rounds of expert meetings were conducted to review and revise an education framework of professional values of nursing undergraduates derived from that theory. Findings A total of 10 studies were included. The contents of two themes were analysed: theories and models and the current status of the professional values development of nursing students. The resulting professional values growth theory for undergraduate nursing students consists of five parts: key aspects, decisive opportunities, drivers, embodiment (humanistic sentiments, moral emotions), and outcomes. A total of five experts in the relevant fields were invited to this study. After two rounds of expert meetings, an education framework for undergraduate nursing students was finally developed, which consists of four parts: education objectives, education process and content, environment and conditions, and evaluation. Conclusion The education framework developed in this study has practical implications for the development of professional values of undergraduate nursing students, providing educational strategies and methods for the growth and internalisation of professional values of undergraduate nursing students.